1912 Ariz. Sess. Laws 253 - (:unkn) unknown (My University, 1912)
§ 24: Prohibited any person from shooting a rifle, revolver, or shotgun of any caliber or gauge from or across any public highway were there are dwelling homes on either side or where the shot shall pass over any cultivated land or dwelling houses, stock, or other animals grazing on land.
Keywords: DISCHARGE